Identification and Prioritization of Factors Affecting the Realization of Sustainable Revenues in Iranian Football Leagues - Asghari, Zahra; Valinejad, Bahman; Naderinasab, Mahdi; Allahyari, Hossien (Future of Work and Digital Management Journal, 2026)
The objective of this study was to identify and prioritize the key factors influencing the realization of sustainable revenues in Iranian football leagues through a mixed-method sequential exploratory design. This research employed a two-phase mixed-method approach. In the first qualitative phase, an extensive literature review was conducted to identify the major themes and determinants of sustainable revenue generation in football leagues. Thematic analysis was performed using NVivo version 14, which yielded seven main themes: revenue diversification, governance and regulation, policy and institutional support, marketing and fan engagement, human resource and talent management, infrastructure and facilities, and economic and environmental context. The analysis continued until theoretical saturation was achieved. In the second quantitative phase, a structured questionnaire was distributed among 20 sports management and financial experts from Tehran, and data were analyzed using SPSS version 26. Descriptive statistics and mean ranking analysis were used to determine the relative importance of each factor in sustaining football league revenues. The results indicated that revenue diversification was ranked as the most critical factor (Mean = 4.82, SD = 0.27), followed by governance and regulation (Mean = 4.68, SD = 0.33) and policy and institutional support (Mean = 4.54, SD = 0.41). Marketing and fan engagement (Mean = 4.41, SD = 0.39) and human resource and talent management (Mean = 4.28, SD = 0.44) were identified as influential but secondary determinants. Infrastructure and facilities (Mean = 4.12, SD = 0.46) and economic and environmental context (Mean = 3.95, SD = 0.52) were ranked lower, suggesting their indirect yet supportive impact on financial sustainability. The study concluded that achieving sustainable revenues in Iranian football leagues requires an integrated framework emphasizing revenue diversification, transparent governance, and supportive institutional policies. Strengthening fan engagement, investing in managerial competence, and developing infrastructural and technological capabilities can further enhance financial stability. The findings provide actionable insights for policymakers, club managers, and investors aiming to modernize and professionalize the financial structure of Iranian football.